DEVELOPMENT, CHARACTERIZATION, AND IN VITRO EVALUATION OF MOUTH DISSOLVING TABLETS OF TAMOXIFEN - Sarad Pawar Naik Bukke; Tamma Avinash Reddy; Narayana Goruntla; Hussaini Bello (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The present study was carried out on Tamoxifen by employing solid dispersion technique. The λmax of phosphate buffer pH 6.8 of Tamoxifen were found to be at 276 nm. The pure drug the optimised Solid dispersion formulations were subjected to FTIR studies. The results were showed that there is no interaction between the drug and excipients. The micrometric properties of blend of Tamoxifen soild dispersion were characterized with respect to Angle of repose, bulk density, tapped density, Carr’s index and Hausner’s ratio. Angle of repose was less than 280, Carr’s index values were 10 to 17 for the pre compression blend of all the batches indicating good to fair flowability and compressibility. Hausner’s ratio was less than 1.2 for all the batches indicating good flow properties. All the tablets of different batches complied with the official requirement of weight variation as their weight variation passes the limits. The hardness of the tablets ranged from 2 to 3 kg/cm2 and the friability values were less than 1% indicating that the tablets were compact and hard. The thickness of the tablets ranged between 3.1 to 3.8 mm. All the formulations satisfied the content of the drug as they contained 96-100% of Tamoxifen and good uniformity in drug content was observed. Thus, all the physical attributes of the prepared tablets were found to be practically within control limits.The dissolution profile of Tamoxifen tablets was compared between solid dispersion tablets. The Tamoxifen solid dispersion tablets showed better release in phosphate buffer pH 6.8, in that F2 showed good drug release i.e., 99.89 at 15 minutes. F2 formulation was taken as optimised formulation.